The Effect of Tax Services, Tax Examination and Taxpayer Awareness on The Level of Taxpayer Compliance at KPP Pratama Padang Sidempuan - A. Asnida (Golden Ratio of Taxation Studies, 2022)
This study aims to examine the effect of Tax Service, Tax Audit and Taxpayer Awareness on the Level of Taxpayer Compliance. The sample of this research is taxpayers who are registered and make tax payments and SPT reporting at KPP Pratama South Makassar, totaling 60 taxpayers. The sampling method is the census method, and the data used is primary data. Data collected by distributing questionnaires which were directly handed over to the respondents. The analytical method used is the Multiple Linear Regression Model with SPSS 16.0 software and to test the hypothesis simultaneously used the F test and Partial used the t-test. The results of the study show that simultaneously Tax Service, Tax Audit and Taxpayer Awareness have a positive and significant effect on the Level of Taxpayer Compliance. And the results of the partial test also the variables Tax Service, Tax Audit and Taxpayer Awareness have a positive and significant effect on the Level of Taxpayer Compliance at KPP Pratama Padangsidimpuan.